A low‐profile and wide‐beam circularly polarized microstrip antenna with resonant structure based on 3/4 λ phase‐shifted sequential rotating feed technology. Issue 3 (5th December 2021) - Wang, Chuang; Cao, Wenquan; Ma, Wenyu; Hong, Rentang
Abstract: A novel single‐layer coplanar‐fed circularly polarized (CP) microstrip antenna is proposed in this article. In order to improve the CP performance, a new sequential rotating feed network based on 3/4 λ (where λ is the wavelength in the medium) phase shift line is adopted in the antenna design, which is on the same plane as the radiating patch to achieve low‐profile characteristics. A curved microstrip resonant structure is loaded around the radiating patch, the half‐power beam width (HPBW) of the antenna is obviously widened. Meanwhile the height is only 0.06 λ 0, thus low profile and wide‐beam characteristics are achieved. In order to prove the effectiveness of the design method, a prototype is fabricated and measured. The measurement results show that it has good impedance matching (from 24.7 to 27.6 GHz) in the 5G mmWave bands. Within the operating bandwidth of the antenna, the HPBW of antenna can reach 125° in xoz ‐plane and 110° in yoz ‐plane. This design method can suitable for 5G mobile communication systems in future.